Peer-Assisted Analysis of Resident Feedback Improves Clinical Teaching: A Case Report. Issue 1 (1st July 2017) - Mai, Christine L.; Baker, Keith
Abstract : Anesthesiologists play an important role in educating future clinicians. Yet few residency programs incorporate teaching skills into faculty development. Consequently, many anesthesiologists have limited training to supervise and educate residents. In turn, these attendings may receive negative feedback and poor evaluations from residents without a means to effectively improve. Peer-assisted teaching between faculty members may serve as a strategy to improve teaching skills. We report a case of peer-assisted analysis of resident feedback to identify specific areas of concern that were targeted for improvement. This approach resulted in improved teaching scores and feedback for the faculty member.